Design, Synthesis and Biological Evaluation of Cinnamic Acyl Shikonin Derivatives. (26th November 2012) - Lin, Hong‐Yan; Chen, Wei; Shi, Jing; Kong, Wen‐Yao; Qi, Jin‐Liang; Wang, Xiao‐Ming; Yang, Yong‐Hua
<x xml:space="preserve">Abstract</x> Inducing apoptosis is an important and promising therapeutic approach to overcome cancer. Here, we described a series of novel synthesized compounds, cinnamic acyl shikonin derivatives (1b–19b), which were synthesized starting from shikonin and cinnamic acids, which exhibit anticancer activity via inducing apoptosis in vitro. Our flow cytometry results showed that compound 8b((E)‐1‐(5, 8‐dihydroxy‐1, 4‐dioxo‐1, 4‐dihydronaphthalen‐2‐yl)‐4‐methylpent ‐3‐enyl‐3‐(3‐(trifluoromethyl) phenyl)acrylate) (IC50 = 0.69, 0.65, 1.62 μm for human SW872‐s, A875 and A549 cell lines, respectively) exhibited conspicuous anticancer activities and has low cell toxicity in vitro. Therefore, we considered that compound 8b is potentially to be a candidate of anticancer agent. The proliferation inhibitory effect of compound 8b was associated with its apoptosis‐inducing effect by activating caspase‐3, caspase‐7, caspase‐9, and PARP. When the level of cleaved caspase‐3, cleaved caspase‐7, cleaved caspase‐9, and cleaved PARP are rise, apoptosis of cancer cells will be induced.